The Pathway to Publishing: A Guide to Quantitative Writing in the Health Sciences - Luby, Stephen; Southern, Dorothy L. (Springer International Publishing : Imprint: Springer, 2022)
Writing manuscripts is central to the advance of scientific knowledge. For an early career aspiring scientist, writing first author manuscripts is an opportunity to develop critical skills and to credential their expertise. Writing manuscripts, however, is difficult, doubly so for scientists who use English as a second language. Many science students intentionally avoid a writing-intensive curriculum. Careful, thorough reviews of draft manuscripts are difficult to secure, and experienced scientific supervisors face more demands on their time than they have time available. Weak draft manuscripts discourage supervising scientists investing the time to coach revisions. It is easier for experienced scientists to ignore the request, or to simply rewrite the article. Early career scientists are motivated to address these barriers but specific advice is difficult to find, and much of this advice is behind a pay wall. This essential, open access text presents writing lessons organized as common errors, providing students and early-career researchers with an efficient way to learn, and mentors with a quick-reference guide to reviewing. Error descriptions include specific examples drawn from real-world experiences of other early-career writers, and suggestions for how to successfully address and avoid these in the future. Versions of this book have been used by Stanford University, UC Davis, Johns Hopkins, and numerous international institutions and organizations for over a decade. This book is licensed under the terms of the Creative Commons Attribution 4.0 International License "http://creativecommons.org/licenses/by/4.0/", which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license and indicate if changes were made The images or other third party material in this book are included in the book's Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the book's Creative Commons license and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder.